Synthesis of coated iron oxide nanoparticles as an additive for nitrile butadiene rubber (NBR) film / Ong Hun Tiar - Ong, Hun Tiar (2016)
Food, pharmaceutical processing and healthcare industries are highly concern about industrial hygiene awareness, thus personal protective equipment (PPE) is compulsory to be used in these industries. NBR gloves are one of the most important PPE but they are possible to tear off and contaminate these products during manufacturing and packaging process. High tendency of torn NBR glove remaining in food or products was due to white or light flesh-coloured glove which was not easy to be detected by naked eyes. With such limitation, iron oxide nanoparticles (IONP) were selected as additive for NBR film to improve the detectability by mean of its magnetic properties. However, IONP has a tendency to agglomerate easily, and thus it is hard to obtain a uniform and well dispersed particle IONP in NBR latex matrix. Hence in this project, IONP was synthesized via precipitation method, coated with fatty acid and compounded with NBR latex to produce a detectable NBR films. The properties of IONPs and coated IONPs were investigated by X-ray Diffractometry (XRD), Raman spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), zeta sizer, Transmission Electron Microscope (TEM), and Vibrating Sample Magnetometer (VSM), Thermal Gravimetric Analyzer (TGA) and sedimentation observation. The properties of C-IONP/NBR film were studied by Universal Testing Machine (UTM), TGA, VSM, FTIR and Scanning Electron Microscopy (SEM). The result shows that, IONP synthesis optimization under reverse precipitation, FeSO4.7H2O as precursor, pour-once method and aging time 1.5 hrs was able to produce small particle size, minimal agglomeration and superior magnetization saturation IONP. Furthermore, 0.6 of oleic acid to IONP ratio and 60 mins ultra-sonication time as coated IONP (C-IONP) was dispersed well in NBR latex. Subsequently, it was found out that 5 phr of C-IONP was excellent to incorporate with NBR latex as it improved slightly in tensile property and induced sufficient magnetic detectability to magnetic detector.